2018
DOI: 10.28945/4138
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Self-Efficacy and Time to Degree Completion of Educational Leadership Doctoral Students

Abstract: Aim/Purpose: This study examined an Ed.D. program redesign to address time to degree completion. The aim was to emphasize the need to improve students’ academic writing and embody a scholarly practitioner approach to research. Background: Doctoral programs have the highest attrition of graduate programs, with almost half of the students taking six to seven years to complete. Methodology: An ex-post-facto correlational research design examined self-efficacy and educational leadership doctoral students percei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Multon et al (1991), through seminal work, investigated the relationship of self-efficacy to academic performance and persistence through a metanalysis on self-efficacy and the results revealed positive and statistically significant relationships among self-efficacy beliefs and academic performance and persistence outcomes. On the contrary, McBrayer et al (2018) found high self-efficacy scores among doctoral students, but did not find a correlation between self-efficacy and time to degree completion warranting further research. Thus, it is important to note, current research has shown a potential explanation of high self-efficacy scores may be indicative of overconfidence as leaders by nature may exhibit confidence in their capabilities due to their chosen leadership field (Matheka et al, 2020).…”
Section: Theoretical Framework: General Self-efficacycontrasting
confidence: 60%
See 3 more Smart Citations
“…Multon et al (1991), through seminal work, investigated the relationship of self-efficacy to academic performance and persistence through a metanalysis on self-efficacy and the results revealed positive and statistically significant relationships among self-efficacy beliefs and academic performance and persistence outcomes. On the contrary, McBrayer et al (2018) found high self-efficacy scores among doctoral students, but did not find a correlation between self-efficacy and time to degree completion warranting further research. Thus, it is important to note, current research has shown a potential explanation of high self-efficacy scores may be indicative of overconfidence as leaders by nature may exhibit confidence in their capabilities due to their chosen leadership field (Matheka et al, 2020).…”
Section: Theoretical Framework: General Self-efficacycontrasting
confidence: 60%
“…In an effort to combat the challenges of time to degree completion, doctoral programs need to be centered around academic writing and scholarly practitioner research (McBrayer et al, 2018). Experiences conducting research have been shown to result in higher degrees of research self-efficacy in doctoral students (Petko et al, 2020).…”
Section: Research Self-efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…These include student's belief, the teacher's belief, and the faculty's belief in the self-efficacy of the students. McBrayer et al (2018) conducted a study about the relationship between self-efficacy and time to degree completion of doctoral study. The study concluded that students with higher self-efficacy end up completing the writing of their dissertation in a shorter time.…”
Section: Writing Efficacy and Self-efficacymentioning
confidence: 99%